Artificial Intelligence in Healthcare: Bridging Innovation and Regulation - Alyousef, Awad; Al-Omari, Omaia (Journal of Ecohumanism, 2025)
Regulations must be clear and stringent for both healthcare providers and patients. Regulations have been progressively refined due to identifying weaknesses within the regulatory process. For example, regulatory principles applied to pharmaceuticals have been extended to cover other medical technologies. This paper provides a solid foundation of the meaning of Artificial Intelligence and machine learning as well as the usage of these technologies in healthcare to provide better diagnosis and more personalised medicine. Also, this paper proposes the challenges and regulation in Artificial Intelligence and machine learning in the healthcare domain. This paper emphasises the importance of establishing regulations for artificial intelligence and machine learning to ensure safety in the healthcare domain.